PENGARUH MAKANAN TAMBAHAN GLIKEMIK TINGGI TERHADAP PENINGKATAN KONSENTRASI BELAJAR SISWA SEKOLAH DASAR - Uken SS Soetrisno; Almasyhuri Almasyhuri; Lies Karyadi (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2005)
ABSTRACTBackground: Lack of both macro and micro nutrients caused the inhibition on mental and intellectual development. Most of the study related to nutritional status of school children indicated the hidden hunger syndrome, where the student did not have breakfast or something to eat during school time which caused low performance in school. Some interventions had been done to improve their school performances, such as giving iron tablets or traditional school lunch three times a week. Neither of those practices gave good results. Process foods especially carbohydrate part can increase its absorbability to make blood glucose in the normal level during study time. The food formulas using processed carbohydrates had been developed to make high glycaemic index snack for school children. Objectives: The study objectives were to evaluate the effect of high glycaemic index foods on school performance of the elementary school children.Methods: Samples came from two diferrent elementary schools were purposively selected into 2 groups. One school as control group and the other one as treatment group. Each school consisted of 3rd + 4th grades and 5th +6th grades, with 56 children per grades. Control groups were given snack foods were bought from vendor around the school, while the treatment groups were given the high glycaemic snack foods prepared in laboratory. Foods were given at break time, every day in the first month of intervention; 3 times a week during the second month and none during the third month. Anthropometric measurement, blood glucose, Hb, Ht and school performances were evaluated every month during intervention. The data were analyzed to compare the changes in all variables measured on all groups using Studentized-t test. Results: Body weight of both groups increased after one month intervention, especially for younger students, and those were significant increase after 3 months intervention. Hemoglobin level did not change significantly, while blood glucose increased in the first and second month of intervention in the treatment group.; it was the opposite of the control group. Daily intervention significantly increased the school performance of the younger students in the treatment group. After 3 months study, the school performance in all groups were higher than that before intervention. Conclusions: High glycaemic snacks foods had smaller portion size than common snack foods sold in the school area, had higher nutrient content, and were accepted well. School performance of treatment group were better than that of control group, especially if the snack food given daily. The results can be implemented on the national school lunch program while promoting the local food based snacks. [Penel Gizi Makan 2005,28(2): 83-91] Keywords: school lunch, high glycaemic index, school performance.